ASUHAN KEPERAWATAN PADA PASIEN DENGAN DIABETES MILETUS DI KAMPUNG SASAK KELURAHAN LIMO KOTA DEPOK, JAWA BARAT - Deswita Risdha Moelyana (2023)
Background : Type 2 diabetes is a type of diabetes that is very common. This disease mostly occurs in adults, caused by genetic elements and unhealthy life habits such as lack of physical activity, obesity and unhealthy eating habits. This research was conducted to analyze the application of nursing care, nursing implementation, and nursing evaluation. The design used is descriptive using the case study method. Participants used were 1 adult client with a medical diagnosis of Type 2 Diabetes Miletus. Results : Nursing problems that arose in the case were blood glucose instability b.d insulin resistance d.d the client said dizziness, ineffective peripheral perfusion b.d hyperglycemia d.d the client said the legs felt cramps and tingling, Disturbance of sleep patterns b.d lack of sleep control. After carrying out nursing actions for 3x24 hours the results of the evaluation of all nursing diagnoses are resolved according to the objectives of the established outcome criteria. Conclusion : The application of nursing care to clients with Diabetes Miletus type 2 achieves the expected results due to good cooperation between nurses, the client's family, and other health teams. Keywords : Adults, Diabetes Miletus type 2, Nursing Care